2001
DOI: 10.1111/j.1745-9125.2001.tb00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Celerity, Impulsivity, and Extralegal Sanction Threats Into a Model of General Deterrence: Theory and Evidence*

Abstract: We propose a model that integrates the extralegal consequences from conviction and impulsivity into the traditional deterrence framework. The model was tested with 252 college students, who completed a survey concerning drinking and driving. Key findings include the following: (1) Although variation in sanction certainty and severity predicted offending, variation in celerity did not; (2) the extralegal consequences from conviction appear to be at least as great a deterrent as the legal consequences; (3) the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
300
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(319 citation statements)
references
References 36 publications
11
300
0
8
Order By: Relevance
“…Economists, for example, use the term ''utility'' to refer to this common but unknown yardstick, but without bothering too much how to measure utility. In the context of drunk-driving, Nagin and Pogarsky (2001) have proposed an ingenious scenario method of evaluating both legal and extra-legal consequences on a common money-based scale, as a first approach to such a generalized Beckerian yardstick in the field of regulatory non-compliance.…”
Section: Rational Choice Theory Of Non-compliancementioning
confidence: 99%
“…Economists, for example, use the term ''utility'' to refer to this common but unknown yardstick, but without bothering too much how to measure utility. In the context of drunk-driving, Nagin and Pogarsky (2001) have proposed an ingenious scenario method of evaluating both legal and extra-legal consequences on a common money-based scale, as a first approach to such a generalized Beckerian yardstick in the field of regulatory non-compliance.…”
Section: Rational Choice Theory Of Non-compliancementioning
confidence: 99%
“…However, this deterrent affect may be short lived. Studies of deterrence have found that extralegal motivators are typically much stronger motivators than fear of legal consequences (Foglia, 1997;Grasmick and Bursik, 1990;Meier and Johnson, 1977;Nagin and Pogarsky, 2001). Based on a literature review, Nagin (1998, p. 20) concluded that, "[I]ndividuals who report higher stakes in conventionality are more deterred by perceived risk of exposure for law breaking."…”
Section: Discussionmentioning
confidence: 99%
“…In this study, according to D'Arcy, Hovav and Galletta [21], we refer "certainty of sanctions to the probability of being published, and severity of sanctions to the degree of punishment" associated with deviant security behavior. Prior deterrence research shows that sanctions negatively impact individual criminal and deviant behaviors [54]. For example, perceived certainty and severity of sanctions are negatively related to employee intention to engage in deviant behaviors [18,40,54].…”
Section: Figure 1 An Integrated Emotion and Gdt Modelmentioning
confidence: 99%
“…Prior deterrence research shows that sanctions negatively impact individual criminal and deviant behaviors [54]. For example, perceived certainty and severity of sanctions are negatively related to employee intention to engage in deviant behaviors [18,40,54].…”
Section: Figure 1 An Integrated Emotion and Gdt Modelmentioning
confidence: 99%